A modelagem matemática e a interdisciplinaridade na introdução do conceito de equação diferencial em cursos de engenharia - Fecchio, Roberto (2011)
The objective of the survey was to investigate the use of Mathematic Modeling allied to the Interdisciplinarity and to Theory of Didactic Situation, such as facilitator resources on the introduction of the concept of differential equation for students of the Engineering basic cycle. The connection between these resources made possible the elaboration, organization, follow-up and analysis of a didactic sequence, constituted by 15 steps, which involved: Experimentation, Abstraction, Resolution and Validation. In this study, the intention was to answer the following question: Interdisciplinarity activities which use the Mathematic Modeling propitious the learning of differential equations? The research was characterized as qualitative, of action research type, performed with 12 students from the 2nd year of an Engineering course from Great ABC region. It was verified that different compounds of the didactic environment structure can be intermingled with the modeling phases, according to Bassanezi (2002), in an auto-reflexive spiral. Such activity, generated by a real problem has as scenario the position of the professor-researcher before a group of students in an environment constituted by laboratories, classroom, questionings and devolutions, based on the didactic situations proposed by Brousseau (2008). The analysis of the data obtained on the experimentation made possible to assert that the interdisciplinary activities led by steps, according to this work s indications, presented new possibilities of motivation, exploration of contents and results available to the Engineering basic cycle s students. It provided to students gains on the teaching and learning process and possibilities on the application of knowledge in new situations. Problems related to Mechanics, Electricity and other aspects of Physics can serve as starting point for other surveys, using the same theoretical frame of references for the study of 1st and 2nd order differential equations